Kontribusi Motivas Diri, Kedisiplinan Belajar dan Dukungan Orang Tua terhadap Prestasi Belajar Otomotif Siswa SMK Negeri 2 Pengasih - Adhawan Priyoutomo; Supriyoko Supriyoko; Suyono Suyono; Rahayu Retnaningsih (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to determine the contribution of the variables of Self-Motivation, Learning Discipline, and Parental Support both partially and simultaneously to student learning achievement in the Automotive Engineering expertise program at SMK Negeri 2 Pengasih. This type of research is included in quantitative correlational research with multiple regression analysis techniques. The entire population was sampled with a total of 104 grade XII students. Data collection used a closed questionnaire and student final exam results documents. The research instrument that has passed the validity and reliability test, then continued with the classical assumption test to ensure that the regression model meets the eligibility requirements. The results showed that the three independent variables contributed significantly to student automotive learning achievement with a value of F = 26.718. Simultaneously with a significance value of 0.000 (p <0.001) and an Adjusted R Square value of 0.428 which means the model is able to explain 42.8% of the variation in learning achievement. Partially, the Self-Motivation variable significantly (p<0.05) provides the largest contribution to student learning achievement with a t-value of 2.120 followed by Learning Discipline with a t-value of 1.992 and Parental Support with a t-value of 2.021. The magnitude of the real contribution of each variable, namely: Self-Motivation of 12.15%, Learning Discipline of 10.49%, and Parental Support of 10.24%. These results emphasize the importance of strengthening students' intrinsic motivation, habituating learning discipline, and active parental involvement to improve learning outcomes in vocational education.